(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Despite the seemingly abundance of solar energy potential in the Northcentral region of Nigeria, only a few studies have been carried out; a few attempts used empirical method which has a lower degree of trustability compared to the geospatial technique. This study conducts a comprehensive geospatial analysis of solar energy potential in the Federal Capital Territory (FCT) and Benue State. Solar radiation and temperature data covering a period of thirty years (1993 – 2022) were obtained from the Nigerian Meteorological Agency (NIMET) and analysed. The solar radiation, temperature, elevation, slope and aspect were ranked based on the analytical hierarchy process (AHP) and the weighted overlay tool was used to produce solar energy potential map for FCT and Benue state. The result shows higher potentials around the beginning and end of the year and lower during the middle months with the lowest radiation values recorded in the month of August in the study areas. The months of January, February, March, November, and December typically offer the highest solar radiation values, making them optimal for solar energy production. The maximum solar radiation values of 4.76 kWh/m2/day and 4.72 kWh/m2/day were recorded in FCT and Benue respectively in the month of February. Areas of high, moderate and low solar energy potentials within the study locations were identified and mapped. Understanding the solar radiation spread can guide policymakers in making informed decisions about where to invest in solar infrastructure.